2015
DOI: 10.1016/j.cplett.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of 1,2-BN cyclohexene using microwave spectroscopy

Abstract: 1,2-BN cyclohexene has been produced from 1,2-BN cyclohexane through the loss of H 2 and characterized and identified using a pulsed-beam Fourier-transform microwave spectrometer. Microwave spectra were measured in the frequency range of 5.5-12.5 GHz, providing accurate rotational constants and quadrupole coupling strengths. Results of high level calculations allowed clear assignment ofthe spectra to1,2-BN Cyclohexene. Heating the initial compound, 1,2-BN Cyclohexane, to 60°C in a 1 atm. neon stream results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…53 The gas phase microwave spectroscopy was applied for the identification and the first characterization of 1,2-BN cyclohexene which was produced from 1,2-BN cyclohexane through the loss of H 2 (i.e., heating sample in a Ne gas stream prior to insertion into microwave cavity) (Scheme 1). 54 This work presented the opportunity to compare the rotational constants and quadrupole coupling strengths for 1,2-BN cyclohexene with the aromatic, planar 1,2-dihydro-1,2-azaborine. The high level calculations were also applied to estimate structural Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…53 The gas phase microwave spectroscopy was applied for the identification and the first characterization of 1,2-BN cyclohexene which was produced from 1,2-BN cyclohexane through the loss of H 2 (i.e., heating sample in a Ne gas stream prior to insertion into microwave cavity) (Scheme 1). 54 This work presented the opportunity to compare the rotational constants and quadrupole coupling strengths for 1,2-BN cyclohexene with the aromatic, planar 1,2-dihydro-1,2-azaborine. The high level calculations were also applied to estimate structural Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…On the other hand, prior to this work, a complementary kinetic analysis of dehydrogenation from the carbonaceous components of these CBN heterocycles remained elusive in our hands due to the lack of effective reaction conditions for this transformation. We had found that, at the elevated temperatures typically required for cycloalkane dehydrogenation, rapid BN hydrogen release occurs first to produce species that are isostructural and isoelectronic with cyclohexenes ( A ; Figure , top) . For all-carbon compounds, it is known that dehydrogenation of a cycloalkene is significantly more facile than that of the corresponding fully saturated cycloalkane.…”
mentioning
confidence: 99%